Immunohistochemical characterization and potential prognostic relevance of dopamine signaling in canine pulmonary adenocarcinoma - Kuzmik, Alana R.; Seelig, Davis M.; Hoeppner, Luke H.; Rendahl, Aaron; Able, Hannah; Wolf-Ringwall, Amber; Lawrence, Jessica (Frontiers in Veterinary Science, 2025)
IntroductionDopamine signaling contributes to tumor progression in human lung adenocarcinoma. Isoforms of dopamine-and-cAMP-regulated phosphoprotein Mr. 32,000 (DARPP-32) are overexpressed in human lung adenocarcinoma and are associated with prognosis and development of treatment resistance. Despite similarities to human lung adenocarcinoma, dopamine signaling has not yet been evaluated in canine pulmonary adenocarcinoma. The objective of this study was to characterize immunohistochemical expression of DARPP-32 isoforms in canine pulmonary adenocarcinoma and assess associations with clinical variables, markers of proliferation and angiogenesis, and outcome.MethodsImmunohistochemistry for DARPP-32 isoforms DARPPN and DARPPC, EGFR, D2R, and VEGFR2 was used to assess 46 canine adenocarcinomas. The percentage of tumor cells positive for target protein expression and staining intensity of DARPPC, DARPPN, and EGFR were quantified using a modified immunohistochemical scoring scheme. Intratumoral vascular endothelial D2R and VEGFR2 expression were quantified based on the number of positive vessels.ResultsDARPPN or DARPPC was expressed in 40 (87%) adenocarcinomas; 54% of tumors expressed both isoforms. DARPPN was positively correlated with tumor volume, VEGFR2 expression and mitotic count. DARPPC was positively correlated with EGFR expression. VEGFR2 expression was positively correlated to EGFR expression and mitotic count. When stratified by the median, survival was shorter with increased tumor volume (p = 0.003) and greater intratumoral VEGFR2 expression (p = 0.042). Dogs with DARPPN (p = 0.059) or DARPPC (p = 0.120) expression greater than the median had shorter survival than those with lower expression.ConclusionCollectively, data support further investigation of DARPP-32 protein signaling in canine lung adenocarcinoma.